Natural history of pleural thickening after exposure to crocidolite. - de,Klerk NH; Cookson,WO; Musk,AW; Armstrong,BK; Glancy,JJ (Br J Ind Med, 1989)
Serial plain chest radiographs of 384 men who worked at the Wittenoom crocidolite mine and mill between 1943 and 1966 and who applied for pneumoconiosis compensation between 1948 and 1982 have been examined independently by two trained observers for pleural disease using the 1980 ILO-UICC classification of radiographs to record width and extent of pleural disease. Radiographs covering follow up periods of from two to 38 years were examined (median number of films per subject was nine). The degree of crocidolite exposure was estimated from employment records and a survey of airborne fibre concentrations performed in 1966. Agreement between the observers on the presence and degree of pleural disease in the final film for each subject was moderately close (Kendall's tau B = 0.62) and was least for subjects with thickening less than 5 mm in width. Diffuse pleural thickening extending for greater than 50% of the lateral chest wall was the most common type recorded by both observers. Minor pleural thickening frequently progressed in extent along the lateral chest wall but progression beyond 5 mm in thickness was less common. Pleural plaques were not seen to progress beyond their initial thickness or extent. The rate of onset of thickening in this population increased continually from the time of first exposure and also increased slightly with age. There was evidence that the level of total cumulative exposure to crocidolite increased the rate of onset of pleural thickening in the period between five and 15 years after first exposure. Rate of progression of established thickening was greatest in subjects who first developed thickening early after first exposure. The relative rate of progression decreased slowly with time from first signs of thickening and there was no evidence of any progression more than 15 years after onset.